2020
DOI: 10.1080/1359432x.2020.1803960
|View full text |Cite
|
Sign up to set email alerts
|

How to design, implement and evaluate organizational interventions for maximum impact: the Sigtuna Principles

Abstract: Research on organizational interventions needs to meet the objectives of both researchers and participating organizations. This duality means that real-world impact has to be considered throughout the research process, simultaneously addressing both scientific rigour and practical relevance. This discussion paper aims to offer a set of principles, grounded in knowledge from various disciplines that can guide researchers in designing, implementing, and evaluating organizational interventions. Inspired by Mode 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 86 publications
3
67
0
1
Order By: Relevance
“…In order for PPOIs to achieve their intended outcomes, actions need to be sustainably implemented (von Thiele Schwarz et al, 2020 ). We argue that the Job Demands Resources model (JD-R) (Demerouti et al, 2001 ) is a suitable framework for developing actions.…”
Section: Creating Healthy Workplaces By Changing Work Policies Practices and Proceduresmentioning
confidence: 99%
“…In order for PPOIs to achieve their intended outcomes, actions need to be sustainably implemented (von Thiele Schwarz et al, 2020 ). We argue that the Job Demands Resources model (JD-R) (Demerouti et al, 2001 ) is a suitable framework for developing actions.…”
Section: Creating Healthy Workplaces By Changing Work Policies Practices and Proceduresmentioning
confidence: 99%
“…On a related note, the results showed that support types integrated into the daily practice and work hours, such as group reflections and peer-support, were most successful in terms of participation rate. The integration of such support initiatives into daily routines requires full support and engagement not only from the managers but also from the leadership of the organization (46). Securing such formal support and resources from stakeholders at all organizational levels often involves a coordinated effort and procedural changes, which will unavoidably take time.…”
Section: Keys To Implementationmentioning
confidence: 99%
“…Although site managers were reluctant to use a formal action planning process, the research team adapted the approach as part of the consultation process. Others have similarly recommended that interventions cannot be implemented in a linear pattern but require iterative adjustments to maximize t [57].…”
Section: Implementation Mechanisms and Processmentioning
confidence: 99%